Pelepasan Hak Atas Tanah Untuk Kepentingan Umum - Ni Ketut Vivin Suganda; Minollah -; Lalu Wira Suhartana (Jatiswara, 2017)
The purpose of this study is to know about the regulation of releasing land rights for public interest and to analyze the settlement of this issue which take place in Lombok Utara district. This thesis uses normative technique, which that examines the documents, using various secondary data such as legislation, court decisions, legal theory, and scholars opinions. regulations of releasing the land for public interest is based on Law Number 2 Year 2012 about Land Procurement for establishment of Public Interest. The disposal of land rights for public interest is done through four stages wich is Planning, preparation, implementation and submitting the results. From that four stages there is a problem in the preparation stage where there is a carelessness from the head official from land office of the district of of North Lombok. Regarding the examination of land rights which are used as land procurement for the public interest so that the issue of double certificate in one land object appeard. The settlement of this issue was conducted through a litigation which is in district court of mataram. Which case number is 156/PDT.G/2012/PN.MTR and in this stages won by the Regent of North Lombok District. and in this stages won by the Regent of North Lombok district and Then the appeal was made to the High Court of Mataram with Number 159/PDT.2013/PT.MTR which is the result won again for the regent of Lombok Utara District and furthermore cassasion was submitted by Sajudin, Sukadip and H.M Syaefudin with number 1795 K/PDT/2014 but gets rejected by the Supreme Court judge.